Profile of Fetal Deaths in Dhahira Region, Oman - Patel, Prakash K. (OMJ, 2008)
OBJECTIVES: To study the profile of reported fetal death cases and describe the circumstances under which these deaths occurred. Methods: This is a retrospective case series study of 154 fetal deaths that occurred in the entire Dhahira region health institutions during a 5 year period (January 2000 and December 2004). The fetal death notification form and mortality meeting summaries were used to ascertain the possible causative factors of fetal death. RESULTS: There were a total of 16923 births and 154 fetal deaths in the region, with fetal death rate of 9.1/1000 total births for the study period. The mean age of the mothers at admission was 29.5 ± 7.3 years. The most common factors related to fetal deaths were congenital anomalies (18.2%) followed by, cord abnormalities (16.9%), IUGR (15.5%), hypertension (14.9%), polyhydramnios (13.6%), gestational diabetes (12.2%), Rh incompatibility (9.7%) and abruptio placentae (6.5%). Approximately 50% of the mothers had a previous pregnancy history of IUGR, preterm, LBW, polyhydramnios, abortion and fetal death. The important contributing factors of fetal death were anemia (47.9%) that needed further investigation. Advanced maternal age, grand multiparity and overweight were also the important associated factors of fetal death in Dhahira region. CONCLUSION: The patients with a previous history of fetal demise should be managed under high risk category with close antepartum surveillance, especially in the last trimester, so as to reduce intrauterine fetal deaths which are mostly attributable to preventable causes.